Peningkatan Kemampuan Kognitif Mata Pelajaran Matematika pada Materi Pecahan Menggunakan Model PjBL pada Siswa Kelas IV Sekolah Dasar - Dena Putri Permatasari; Hendra Erik Rudyanto; Fida Rahmantika Hadi (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2024)
This research was motivated by the low cognitive abilities of students. The cause of this problem is the learning process which is still dominated by teachers. This research aims to determine the application of the PjBL model to improve the cognitive abilities of mathematics subjects in class IV elementary school students' fraction material. The type of research used is classroom action research (PTK) which is carried out in two cycles. The research procedures used are planning, implementation, observation and reflection. The subjects of this research were teachers and students of class IV at SDN Karangmalang 2, totaling 7 students. This research data is in the form of observation results and evaluation sheets. The results of this research show an increase in planning for implementing learning using the PjBL model, namely in cycle I the percentage was 57.14%, increasing in cycle II to 85.71%, this indicates an increase from cycle I of 28.57%. From the student aspect, the implementation of the learning process using the PjBL model has increased from cycle I. The average obtained by students was 74.28 with quite an increase in qualifications in cycle II to 85.57 with very good qualifications. Therefore, it can be concluded that the PjBL model can improve students' cognitive abilities.